Potential of a new seed propagated elephant grass cultivar for lignocellulosic bioethanol production via alkaline pretreatment - Camelo, Alessandra (2020)
The new elephant grass PCEA (P. purpureum x P. purpureum) was specifically developed to meet Brazilian tropical conditions and is the first seed propagated genotype worldwide to be launched by Embrapa Dairy Cattle (CNPGL). The advancement of lignocellulosic bioethanol in Brazil faces numerous challenges, including efficient pretreatments designed for each raw material. In this context, the effect of alkaline pretreatment on PCEA biomass was evaluated to infer about its potential for lignocellulosic bioethanol. The experimental design approached three factors: NaOH %w/v ranging from 1.0 to 3.0 varying on 0.5 %w/v, Temperature (T) from 80 to 120 varying on 20 °C and Reaction Time (RT) from 15 to 35 min varying on 5 min each. The effect of the factors was evaluated considering the response variables of biomass recovery, cellulose and hemicellulose yield, in addition to lignin removal. The untreated biomass and the 17 samples generated from assays were dried and characterized regarding its composition following NREL protocols. The untreated biomass of PCEA presented 31.79±1.55 %wt. of cellulose, 15.51±0.70 %wt. of hemicellulose and 18.23±0.45 %wt. lignin. The observed ash content of 3.94±0.07 %wt. is also important for bioenergy crops, it is desirable on lower values for energy conversion. In addition, the content of 20.54±0.11 %wt. extractives on PCEA indicates further potential to generate biofuels through thermochemical routes. After the alkaline pretreatment, the highest cellulose yield of 58.59 %wt. was achieved in assay 14 at 100 ºC, 25 min of RT and NaOH 3% (w/v). Contrary to initial expectations, only alkali concentration statistically differed at 95% confidence level analysis for the full quadratic model at a coefficient of determination (R2) of 0.78. In contrast, hemicellulose as response for linear with interactions model was significant at 95% confidence level (p-value 0.022), which suggests that the interaction of the three factors altogether had an effect on hemicellulose yield. The highest hemicellulose yield of 25.52 %wt. was reached in assay 9 at 80 ºC, 25 min of RT and 2 %w/v concentration of NaOH. The alkali alone had a p-value of 0.000 (ANOVA at 95% confidence level), which suggests an effect of this factor on biomass recovery. The same was not true for the square and linear with interactions models that presented p-values of 0.231 and 0.353, respectively. The coefficient of determination (R2) for the full quadratic model was 0.92 and the highest recovery of 67.92 %wt. was obtained at the 1.0 %w/v NaOH, at 100 °C and 25 min (assay 13). In conclusion, the optimal condition of the design was established considering efficiency in means of maximal lignin removal without degradation of cellulose, which was achieved at 100 ºC, 25 RT and 3 %w/v NaOH with 99.03 %wt. recovery of cellulose and 73.76 %wt. of lignin removal. These results suggest an exciting potential of the new PCEA for lignocellulosic bioethanol production via alkaline pretreatment to be further explored by the Brazilian agroenergy sector. However, further studies should be carried out with enzymatic hydrolysis to confirm high yield of fermentable sugar and consequently, bioethanol.